QualitQUALITY OF LIFE OF STUDENTS WITH VISUAL DISABILITY PRACTITIONERS OF GOALBALLy of life of students with visual disability practitioners of goalball - Tavares, Renato Vitor da Silva; Fumes, Neiza de Lourdes Frederico (UNESP, 2021)
The study aimed to analyze the quality of life of students with visual disability practitioners of goalball according to their education level. The sample was twelve students with visual disability with an average age of 32.7 ± 15.8 years, divided into two groups (1 – Elementary School/Secondary School and 2 – High School/Higher Education). Initially, an anamnesis interview was used to characterize the participants and, then, the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) was applied to collect the data of quality of life. The Student's t-test for independent samples was used to test the differences between the quality of life and education level. Furthermore, Cohen's d-test was adopted to evaluate the size effect. While results, the Elementary/Secondary School group had better scores than the High School/Higher Education group in six domains (functional capacity, limitation by physical aspects, pain, general health status, vitality, and social aspects) of the eight totals of the quality of life. However, the values were statistically significant (p≤0,05) only in the domains of general health status, vitality, and social aspects. Therefore, individuals with lower educational levels presented better self-perception of quality of life in most domains, so it can be concluded that schooling can have a fundamental role in the quality of life of people with visual disability in this research, influencing their perceptions about the variables studied. Received on: 2021/01/20 Reformulated on: 2021/03/29 Accepted: 2021/04/21